2010
DOI: 10.1002/stem.502
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt/β-Catenin Regulation of Liver Receptor Homolog-1 Mediates Pluripotency Gene Expression  

Abstract: Delineating the signaling pathways that underlie ESC pluripotency is paramount for development of ESC applications in both the research and clinical settings. In culture pluripotency is maintained by leukemia inhibitory factor (LIF) stimulation of two separate signaling axes: Stat3/Klf4/Sox2 and PI3K/Tbx3/Nanog, which converge in the regulation of Oct4 expression. However, LIF signaling is not required in vivo for self-renewal, thus alternate signaling axes likely mediate these pathways. Additional factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 56 publications
5
136
2
Order By: Relevance
“…RNAi knockdown of each Oct4, Sox2, or Nanog each caused largely overlapping effects on gene expression, consistent with each gene product regulating a common set of target genes (Loh et al 2006). Many genes regulated by Oct4, Sox2, and Nanog include factors that play a downstream, yet important role in self-renewal, including Klf4, c-myc, Esrrb, Tbx3, and Nr5a2 (Gu et al 2005;Ivanova et al 2006;Jiang et al 2008;Kim et al 2008;Hall et al 2009;Wagner et al 2010). Together, these data are consistent with Oct4, Sox2, and Nanog being the central components of a feed-forward network of transcription factors that drives self-renewal of pluripotent cells (see Fig.…”
Section: Intrinsic Transcription Factor Network Support Pluripotent mentioning
confidence: 64%
See 1 more Smart Citation
“…RNAi knockdown of each Oct4, Sox2, or Nanog each caused largely overlapping effects on gene expression, consistent with each gene product regulating a common set of target genes (Loh et al 2006). Many genes regulated by Oct4, Sox2, and Nanog include factors that play a downstream, yet important role in self-renewal, including Klf4, c-myc, Esrrb, Tbx3, and Nr5a2 (Gu et al 2005;Ivanova et al 2006;Jiang et al 2008;Kim et al 2008;Hall et al 2009;Wagner et al 2010). Together, these data are consistent with Oct4, Sox2, and Nanog being the central components of a feed-forward network of transcription factors that drives self-renewal of pluripotent cells (see Fig.…”
Section: Intrinsic Transcription Factor Network Support Pluripotent mentioning
confidence: 64%
“…Perhaps the best illustration of co-occupancy came from ChIP-seq experiments, which showed that of the 1369 known genes identified as Tcf3-bound, 1173 were also bound by Oct4, and 942 were bound by each, Tcf3, Oct4, Sox2, and Nanog (Marson et al 2008). Other studies showed Oct4 and Nanog mRNA and protein levels were increased when Tcf3 was knocked down or ablated (Pereira et al 2006;Cole et al 2008;Tam et al 2008;Salomonis et al 2010;Wagner et al 2010). Transcriptional profiling of Tcf3 2/2 ESCs showed that Tcf3 ablation caused strongly opposite effects on gene expression compared with Oct4 knockdown and Nanog knockdown (Loh et al 2006;Yi et al 2008).…”
Section: Potential Tcf-independent Mechanismsmentioning
confidence: 99%
“…This discrepancy is likely because RA signaling in reprogramming is dose-and time-dependent, which could be overshadowed by the retrovirus delivery approach. Recent evidence also suggests that Lrh-1 acts downstream of canonical Wnt signaling and regulates the Nanog and Tbx3 pluripotency signaling axis (44), which may explain the ability of expressing Lrh-1 to reliably reset EpiSCs to ground state pluripotency (45). Therefore, Lrh-1 could promote activation of other key pluripotency genes at late stages of reprogramming besides the synergic interaction with Rarg in early Oct4 activation and stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Wagner et al [21] used a combination of pharmacological and genetic methods to implicate liver receptor homolog-1 (Lrh-1) as a novel b-catenin target gene required for maintaining proper levels of Oct4 and Nanog in mESCs. They have postulated that this signalling axis might represent the in vivo counterpart of the LIF -STAT3 pathway (which is only required in vitro) [21].…”
Section: Defining and Maintaining A Pluripotent 'Ground State'mentioning
confidence: 99%
“…They have postulated that this signalling axis might represent the in vivo counterpart of the LIF -STAT3 pathway (which is only required in vitro) [21].…”
Section: Defining and Maintaining A Pluripotent 'Ground State'mentioning
confidence: 99%